2012
DOI: 10.1016/j.pain.2011.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and aetiology of neuropathic pain in cancer patients: A systematic review

Abstract: Pain in cancer patients remains common and is often associated with insufficient prescribing of targeted analgesia. An explanation for undertreatment could be the failure to identify neuropathic pain mechanisms, which require additional prescribing strategies. We wanted to identify the prevalence of neuropathic mechanisms in patients with cancer pain to highlight the need for detailed assessment and to support the development of an international classification system for cancer pain. We searched for studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
221
4
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(245 citation statements)
references
References 33 publications
6
221
4
14
Order By: Relevance
“…2,3 The results of this system can be because of traumatic lesions, inflammation, infections, cancer infiltrations, as well as because of consequences derived from pharmacological treatments (for example, chemotherapy and anti-retroviral therapy). [4][5][6][7] Traumatic lesions of the somatosensory system lead to the onset of neuropathic pain, characterized by spontaneous pain, allodynia and hyperalgesia. 8 Traffic collisions are the main cause of nerve injury, affecting over 3.2 million people worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The results of this system can be because of traumatic lesions, inflammation, infections, cancer infiltrations, as well as because of consequences derived from pharmacological treatments (for example, chemotherapy and anti-retroviral therapy). [4][5][6][7] Traumatic lesions of the somatosensory system lead to the onset of neuropathic pain, characterized by spontaneous pain, allodynia and hyperalgesia. 8 Traffic collisions are the main cause of nerve injury, affecting over 3.2 million people worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of over 13,000 cancer patients the prevalence of neuropathic pain was estimated to be between 19 and 39% [4]. A rational approach to the treatment of neuropathic pain is described in the most recent NICE guidelines [8].…”
Section: When To Use Topiceuticals?mentioning
confidence: 99%
“…Whilst for many an approach using the analgesic ladder will alleviate symptoms, there are many for whom strong opioids fail to control pain. It has been recently postulated that one mechanism for this could be failure to recognise neuropathic pain and targeting treatment towards it [4]. Sources of neuropathic pain in this population include chemotherapy induced peripheral neuropathy and chronic post-surgical pain (which includes scar hypersensitivity) from curative and palliative surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Tumour invasion into or compression of neural structures can cause neuropathic cancer pain [165]. In patients with cancer-related pain, a systematic review from 2012 found a prevalence of neuropathic pain of almost 40% (when patients with mixed pain were included) [18].…”
Section: Some Basic Definitionsmentioning
confidence: 99%